Biochemical biomarkers in Nile tilapia (Oreochromis niloticus) after short-term exposure to diesel oil, pure biodiesel and biodiesel blends - Nogueira, Lílian [UNESP]; Sanches, Ana Letícia Madeira [UNESP]; da Silva, Danilo Grünig Humberto [UNESP]; Ferrizi, Vítor Cid [UNESP]; Moreira, Altair Benedito [UNESP]; de Almeida, Eduardo Alves [UNESP] (Elsevier, 2011)
Fossil fuels such as diesel are being gradually replaced by biodiesel, a renewable energy source, cheaper and less polluting. However, little is known about the toxic effects of this new energy source on aquatic organisms. Thus, we evaluated biochemical biomarkers related to oxidative stress in Nile tilapia (Oreochromis niloticus) after two and seven exposure days to diesel and pure biodiesel (B100) and blends B5 and B20 at concentrations of 0.01 and 0.1mLL -1. The hepatic ethoxyresorufin-O-deethylase activity was highly induced in all groups, except for those animals exposed to B100. There was an increase in lipid peroxidation in liver and gills in the group exposed to the higher concentration of B5. All treatments caused a significant increase in the levels of 1-hydroxypyrene excreted in the bile after 2 and 7d, except for those fish exposed to B100. The hepatic glutathione-S-transferase increased after 7d in animals exposed to the higher concentration of diesel and in the gill of fish exposed to the higher concentration of pure diesel and B5, but decreased for the two tested concentrations of B100. Superoxide dismutase, catalase and glutathione peroxidase also presented significant changes according to the treatments for all groups, including B100. Biodiesel B20 in the conditions tested had fewer adverse effects than diesel and B5 for the Nile tilapia, and can be suggested as a less harmful fuel in substitution to diesel. However, even B100 could activate biochemical responses in fish, at the experimental conditions tested, indicating that this fuel can also represent a risk to the aquatic biota. © 2011 Elsevier Ltd.
Keywords: Biodiesel; Biomarker; Diesel oil; Oreochromis niloticus; Oxidative stress; 1-Hydroxypyrene; Adverse effect; Aquatic biota; Aquatic organisms; Biochemical response; Biodiesel blends; Ethoxyresorufin-O-deethylase; Experimental conditions; Glutathione peroxidase; Glutathione-S-transferase; Lipid peroxidation; New energy sources; Nile tilapia; Renewable energy source; Short-term exposure; Super oxide dismutase; Toxic effect; Biomarkers; Diesel fuels; Fish; Fossil fuels; Fuels; Oxygen; Toxicity; 1 hydroxypyrene; biochemical marker; biodiesel; biological marker; catalase; diesel fuel; ethoxyresorufin deethylase; glutathione peroxidase; glutathione transferase; superoxide dismutase; alkene; aquatic organism; biochemical composition; biomarker; concentration (composition); diesel; enzyme activity; fossil fuel; functional morphology; lipid; oil pollution; oxidation; perciform; physiological response; pollution exposure; toxicity; aquatic species; biota; controlled study; evaluation; gill; lipid peroxidation; nonhuman; oxidative stress; risk; Animals; Biofuels; Catalase; Cytochrome P-450 CYP1A1; Gasoline; Gills; Glutathione Transferase; Lipid Peroxidation; Oxidative Stress; Superoxide Dismutase; Tilapia; Water Pollutants, Chemical; Animalia